IMPLEMENTASI KEBIJAKAN PERMENDES NOMOR 6 TAHUN 2020 BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) BAGI MASYARAKAT MISKIN TERDAMPAK COVID-19 DI DESA JUAI KECAMATAN TANJUNG KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
Direct village fund cash assistance is sourced from the Village Fund to reduce the economic impact due to the Covid-19 pandemic. Government programs that have short-term compensation in helping the poor, more precisely, households that are classified as poor are entitled to receive this assistance. The purpose of this study was to find out and analyze how the implementation of the Village Fund Direct Cash Assistance program in Juai Village, Tanjung Subdistrict, Tabalong Regency, in knowing what criteria the poor are entitled to and are more appropriate to be given priority assistance. Poor families who meet the following criteria: Poor families who are not included in the recipients of PKH, BPNT, and Pre-Employment Card assistance, Poor families who have lost their livelihoods due to Covid-19, and Have family members who are prone to chronic illness in accordance with PERMENDES Number 6 Year 2020 . This study used a qualitative descriptive research method. The research data collection was obtained from conducting interviews with 5 informants. The data analysis technique used in this study is an interactive model of data analysis, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study are that the Implementation of Village Fund Direct Cash Assistance is in accordance with Permendes Number 6 of 2020 for Poor Communities Affected by Covid-19 in Juai Village, Tanjung Subdistrict, Tabalong Regency. Keywords: Policy, Direct Cash Assistance, Covid-19.